Correlation analysis of serum Hcy, HMGB1, and TLR4 levels and mononuclear macrophage polarization in acute cerebral infarction: Serum Hcy, HMGB1, and TLR4 levels and mononuclear macrophage polarization in ACI - Chen, Yinxin; Tan, Taotao (Journal of Medical Biochemistry, 2025)
[Objective] To explore the correlations between homocysteine (Hcy), high mobility group protein B1 (HMGB1), and Toll-like receptor 4 (TLR4) levels and the polarization of mononuclear macrophages among individuals who were admitted with acute cerebral infarction (ACI).[Methods] The case group was made up of 214 ACI patients who were admitted to the hospital between August 2022 and August 2024, whereas the control group was made up of 100 healthy people who had physicals over the same time frame.  A comparison was made between the two groups' admission serum Hcy, HMGB1, and TLR4 levels. The polarization conditions of the mononuclear macrophages in the two groups were compared [proportion of M1-type cells, proportion of M2-type cells, M1/M2 ratio, M1-type polarization markers (interleukin-1β, tumor necrosis factor-α), and M2-type polarization markers (interleukin-10, transforming growth factor-β)]. to investigate the connections between the polarization of mononuclear macrophages and the levels of Hcy, HMGB1, and TLR4 in ACI patients, as well as the associations between these levels and the prognosis of ACI patients. Serum levels of Hcy, HMGB1, and TLR4 were compared between the ACI patients who were split into groups with excellent and poor prognoses. The prognostic efficacy of Hcy, HMGB1, and TLR4 for the prognosis of ACI patients was evaluated using receiver operating characteristic (ROC) curves.[Results] Serum Hcy, HMGB1, and TLR4 levels in the case group were considerably higher (P
Keywords: Acute cerebral infarction; Homocysteine; High mobility group protein B1; Toll-like receptor 4; Mononuclear macrophage polarization; Prognosis-related analysis